Leveraging AI-Powered Writing Assistants to Enhance L2 Writing Proficiency: A Mixed-Methods Study - Khany, Reza; Barzan, Pooria (AI and Tech in Behavioral and Social Sciences, 2026)
This mixed-methods study investigates the efficacy of Grammarly, an AI-powered writing assistant, in enhancing L2 English writing proficiency among 60 intermediate-to-advanced learners at Ilam University. Over a 12-week intervention, an experimental group  (n=30) used Grammarly for essay drafting and revision, while a control group  (n=30) received traditional teacher and peer feedback. Quantitative analysis of pre/post writing assessments revealed significantly greater improvements in the experimental group for linguistic accuracy, coherence, and syntactic complexity  (p